2014
DOI: 10.7314/apjcp.2014.15.8.3797
|View full text |Cite
|
Sign up to set email alerts
|

BMI1 and TWIST1 Downregulated mRNA Expression in Basal Cell Carcinoma

Abstract: Background: BMI1, TWIST1 and SNAI2/SLUG have been implicated in aggressive behavior of squamous cell carcinoma (SCC) and melanoma and BMI1 expression could identify subtypes of Merkel cell carcinoma (MCC). However, BMI1, TWIST1 and SNAI2 expression levels in basal cell carcinomas (BCCs) have not been elucidated. We hypothesized BCC could be a good model system to decipher mechanisms which inhibit processes that drive tumor metastasis. The aim of this study was to examine the mRNA expression level of BMI1, TWIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…There was accumulating evidence revealing that incidence of skin cancer varied in different ethnic backgrounds (Capell et al, 2009;Lin et al, 2011). Among these malignancies, basal cell carcinoma was known as the most frequent type of skin cancer (Rajabpour FV et al, 2014). The following malignancies in skin were cutaneous squamous cell carcinoma and melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…There was accumulating evidence revealing that incidence of skin cancer varied in different ethnic backgrounds (Capell et al, 2009;Lin et al, 2011). Among these malignancies, basal cell carcinoma was known as the most frequent type of skin cancer (Rajabpour FV et al, 2014). The following malignancies in skin were cutaneous squamous cell carcinoma and melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BCC could be a good model system to elucidate mechanisms which inhibit processes that drive tumor metastasis. Although up regulation of BMI1 and TWIST1 have been reported in aggressive SCC, melanoma and metastatic BCC, a recent study showed decreased levels of BMI1 and TWIST1 mRNA expression in non-metastatic BCCs (Rajabpour et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…BCC, with its rarely metastatic and less aggressive behaviour, can be a good in vivo model to study the potentially intrinsic inhibitory mechanism that can attenuate aggressiveness and metastasis. We previously reported downregulation of BMI1 and TWIST1 mRNA expression in nonmetastatic BCC samples compared with controls . We extended our research and hypothesized that BCC can be a rarely metastatic cancer model, and we aimed to understand the potentially metastatic attenuating features in BCC with focus on the EMT and stemness regulatory molecular network.…”
mentioning
confidence: 79%
“…Histopathological data was double‐checked, and results demonstrated that 55% of the BCC tumours had mixed pathology and 45% had nonmixed pathology results. In addition, based on the aggressiveness and invasiveness as indicated by the histopathology results, the BCC tumours were divided into high‐risk (53·3%) and low‐risk (46·7%) groups, as described previously …”
mentioning
confidence: 99%